Do Bank-Affiliated Analysts Benefit from Lending Relationships? - CHEN, TING; MARTIN, XIUMIN (Journal of Accounting Research, 2011)
This paper investigates whether private information from lending activities improves the forecast accuracy of bank-affiliated analysts. Using a matched sample design, matching by affiliated bank or borrower, we demonstrate that the forecast accuracy of bank-affiliated analysts increases after the followed firm borrows from the affiliated bank. We also find that the increase in forecast accuracy is more pronounced for borrowers with greater information asymmetry and bad news, and for deals with financial covenants. Last, we find that the informational advantage of bank-affiliated analysts exists only when the affiliated banks serve as lead arrangers, not merely as participating lenders. Overall, our evidence suggests that information flows from commercial banking to equity research divisions within financial conglomerates.